Development of a system theory-based environmental sustainability management framework for higher education institutions - Del Fierro-Juan, Nerissa D.
The world is in the state of extraordinary emergency due to major environmental issues. Education is recognized as a key solution to promoting environmental sustainability. HEIs, in particular have a significant role in fostering environmental stewardship, as evidenced by various international sustainability declarations. Despite this, there remains a pronounced gap between policy rhetoric and actual practices in HEIs, with many institutions struggling to implement effective environmental sustainability programs. This qualitative research establishes the context and significance of environmental sustainability, particularly within higher education institutions using multiple case studies of three model HEIs in the Philippines. It provides an overview of relevant literature and highlights the inadequacy of previous research, thereby establishing the relevance of this study and the theoretical framework it employs. It answers the problem: How can Philippine HEIs adopt the systems theory approach in formulating their environmental management program? It underscores the need for a robust framework to address this issue, highlighting the inconsistency and lack of coordination in existing efforts. This study aims to fill this gap by proposing a systems theory-based framework for environmental sustainability in HEIs, linking educational administration to instruction, research, and extension services. A comprehensive environmental sustainability management model for Philippine HEIs, was provided to offer a pathway for these institutions to become genuine agents of societal change through educational administration and best practices.